Dislocated cone metric space over Banach algebra and α-quasi contraction mappings of Perov type - Reny George; R Rajagopalan; Hossam A Nabwey; Stojan Radenović (Fixed Point Theory and Applications, 2017)
Abstract A dislocated cone metric space over Banach algebra is introduced as a generalisation of a cone metric space over Banach algebra as well as a dislocated metric space. Fixed point theorems for Perov-type α-quasi contraction mapping, Kannan-type contraction as well as Chatterjee-type contraction mappings are proved in a dislocated cone metric space over Banach algebra. Proper examples are provided to establish the validity of our claims.